ENT 530 Case Study: Franky Wiyu / Zahra' Mardhiah Mustafa - Mustafa, Zahra' Mardhiah (2021)
FRANKY WIYU ART are selling merchandise products that are enamel pins from sellers' artwork. Our business offers affordable prices to our beloved customers. Our target audience is a student and art lover. Our product actually be done and deal online and we do not require to have a face- to- face. The marketing strategy that is used by FRANKY WIYU ART are promoting thru media social, affordable price and trending enamel pin design. This strategy will attract customers and pay attention as we value the customer's wants and needs.